Tribological behavior of Mg–3.5 vol% TiO2 composite at room and elevated temperatures - Sh. Arbabi; H.M. Ghasemi; R. Mahmudi (Journal of Materials Research and Technology)
Pure magnesium (Mg) and magnesium with 3.5 vol% titanium dioxide (Mg–3.5 vol% TiO2) samples were produced using powder metallurgy and extrusion processes. The mechanical properties of the samples were evaluated through shear punch and hot hardness tests over a temperature range of 25–200 °C. The dry tribological behavior of samples was investigated using a pin-on-disk tribometer at a sliding speed of 0.4 m/s, a sliding distance of 1000 m under normal loads of 5–100 N at both room temperature and an elevated temperature of 150 °C. The addition of TiO2 improved wear resistance, hardness, and strength. However, both pure Mg and the composite showed approximately similar wear rates under normal loads of 5 N and 20 N at room temperature, as well as under a normal load of 5 N at 150 °C. As the normal load was increased, the composite sample exhibited superior wear behavior compared to pure Mg. Additionally, it was found that oxidation was the primary wear mechanism at room temperature for both materials. At the wear temperature of 150 °C under normal loads of 5 N and 20 N, oxidation remained dominant for the composite, but under higher loads, severe plastic deformation became the primary wear mechanism.